2020
DOI: 10.1186/s12888-020-2448-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mental distress among undergraduate students in northern Tanzania

Abstract: Background: Mental distress is a major public health problem which includes anxiety, depression and somatic symptoms such as sleeping problems, fatigue and headache. University students are consistently reported to have higher levels of mental distress compared to the general population. Although university students with mental distress have significantly impaired cognitive functioning, learning disabilities and poor academic performance, the burden of this problem in Tanzania is unknown. This study aimed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
3
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 20 publications
4
32
3
6
Order By: Relevance
“…This may be related to gender differences in seeking psychological help in China, where male students are less likely to utilize mental health services 44 . Inconsistent with results of previous studies 45 , no association was found between family history of mental disorders and depression in either of the sites. Data on family history of mental disorders were collected by self-report in this study, which method is less reliable due to fear of stigma and discrimination.…”
Section: Discussionsupporting
confidence: 74%
“…This may be related to gender differences in seeking psychological help in China, where male students are less likely to utilize mental health services 44 . Inconsistent with results of previous studies 45 , no association was found between family history of mental disorders and depression in either of the sites. Data on family history of mental disorders were collected by self-report in this study, which method is less reliable due to fear of stigma and discrimination.…”
Section: Discussionsupporting
confidence: 74%
“…Starting university seems to constitute a crucial period for the mental health of students (Molina et al, 2012;Pedrelli et al, 2015;Auerbach et al, 2016;Harris, 2019), who consistently report higher levels of distress compared to the general population (Stallman, 2010;Dachew et al, 2015;James et al, 2017;Tariku et al, 2017;Mboya et al, 2020). Previous research shows that 19.2-32% of university students reports mental health problems and subsyndromal symptoms (Stallman, 2010;Abdolhossini and Shikhmohamadi, 2012;Auerbach et al, 2016).…”
Section: Introduction University Students' Distressmentioning
confidence: 99%
“…Histórico familiar de doença mental também se mostrou associado à prevalência de sintomas depressivos (Mboya et al, 2020). No estudo de Flesch et al (2020), 56% dos alunos relataram ter história familiar de depressão e nos resultados de Rehmani (2018), 14% dos alunos têm um histórico familiar positivo de depressão.…”
Section: Discussionunclassified
“…Os aspectos acadêmicos também influenciam a ocorrência de depressão entre os estudantes universitários e os sintomas depressivos permaneceram significativamente associados ao baixo desempenho acadêmico (Sibnath et al, 2016;Ngin et al, 2018;Flesch et al, 2020), à obtenção de notas indesejadas (Othman et al, 2019;Mboya et al, 2020;Gul et al, 2020), menor satisfação com a escolha acadêmica (Piumatti, 2018;Leão et al, 2018), além de não estar no curso escolhido como primeira opção (Leão et al, 2018) e à preocupação em encontrar um emprego (Othman et al, 2019). A maior prevalência de depressão pode reduzir a qualidade de https://textura.famam.com.br/textura v.14, n.2, 2020 vida do estudante, resultando em perda do controle pessoal, dificuldade na capacidade de aprendizagem consequentemente menor produtividade, diminuição do desempenho acadêmico e tentativa de suicídio (Dagnew, 2020).…”
Section: Discussionunclassified